The search for essence: ’Africanness’ in 20th century South African architecture - Marschall, S. (Southern African Humanities, 2021)
Throughout South Africa’s recent architectural history, some architects have attempted to imbue their buildings with a specifically African character or evoke a sense of ’Africanness’. This article investigates the signs considered appropriate to convey Africanness, the concept of Africa conveyed and the intentions behind the ’Africanising’ of architectural design. The first example of such ’Africanising’ was Moerdijk’s Pretoria University library building, with sculptural decoration reminiscent of Egypt and Great Zimbabwe. Such references to what were perceived to be the only precedents of ’high civilizations’ on the African continent clearly speak of Afrikaner nationalism underlying the regionalist tradition. Eaton was a key representative of this tradition, though his perspective with respect to Africa was much broader and his passion for Africa all-encompassing. In the 1950s and 60s, several architects developed a strong interest in incorporating contemporary African or Afrophile art into their architecture. This constituted an important shift from Eaton’s pan-African, atemporal focus on tradition towards the recognition of a changing, contemporary urban South African culture.